(3GdLGeY GdeUfa aj TYH GdEjeGfs - (3CHh HcQ CMeO Hf GdMSjf Hf Ydj GdNQGSGfj GdTGaYj, GdHjgbj,J (B458 (3g` s
(3ChdgG (B:s
(3jHOC HaUd ai JYde GdbQBf s
(3BNQgG (B:s
(3jfJgi HGdHGH GdKGfi hGdKdGKhf ef TYH GdGjeGf hgh HGH ai GdEaGA HGdYghO s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B116 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B206s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B574s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs